2012
DOI: 10.1007/s10741-012-9346-7
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mitochondrial function in cardiac hypertrophy and heart failure

Abstract: Normal cardiac function requires high and continuous supply with ATP. As mitochondria are the major source of ATP production, it is apparent that mitochondrial function and cardiac function need to be closely related to each other. When subjected to overload, the heart hypertrophies. Initially, the development of hypertrophy is a compensatory mechanism, and contractile function is maintained. However, when the heart is excessively and/or persistently stressed, cardiac function may deteriorate, leading to the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 118 publications
1
40
0
Order By: Relevance
“…ATP is primarily produced in the mitochondrial respiratory chain by OXPHOS. Previous studies showed that a dysfunction of mitochondrial bioenergetics contributes to the cardiac hypertrophy and can lead to heart failure (Wilkins et al ., ; Osterholt et al ., ). Mitochondrial changes during cardiac hypertrophy include disrupted mitochondrial substrate metabolism, respiratory chain activity and proteomic remodelling as well as oxidative stress (Marin‐Garcia et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…ATP is primarily produced in the mitochondrial respiratory chain by OXPHOS. Previous studies showed that a dysfunction of mitochondrial bioenergetics contributes to the cardiac hypertrophy and can lead to heart failure (Wilkins et al ., ; Osterholt et al ., ). Mitochondrial changes during cardiac hypertrophy include disrupted mitochondrial substrate metabolism, respiratory chain activity and proteomic remodelling as well as oxidative stress (Marin‐Garcia et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Finally, it should be noted that four out the nine patients had left ventricular hypertrophy. Mitochondrial function could therefore be further deteriorated (26,32) apart from the ischemia related dysfunction, but because of the limited number of patients, meaningful subgroup analyses could not be done.…”
Section: Discussionmentioning
confidence: 99%
“…As the engine of the generation of energy and reactive oxygen species (ROS) [12], the mitochondrion plays an important role in the myocardium. The heart, which is an organ with a high energy consumption, also exhibits changes or impairment in mitochondrial function during the progression of hypertrophy or heart failure [13]. Some studies reported that treatment with atorvastatin could regulate the metabolism of the myocardium [14].…”
Section: Introductionmentioning
confidence: 99%